Strategi Pemerintah Daerah Dalam Meningkatkan Pendapatan Asli Daerah Di Kabupaten Bolaang Mongondow Utara - Aneta, Asna; Yuliyani Solihin, Dwi Indah; Aneta, Yanti; Podungge, Abdul Madjid; Podungge, Abdul Wahab; Hunawa, Robby (Fakultas Ilmu Sosial dan Ilmu Poliitik Universitas Ichsan Gorontalo, 2025)
The phenomenon of problems faced in increasing the productivity of the State Civil Apparatus (ASN) in Indonesia is closely related to the mismatch between the composition of positions and the competencies possessed by ASN. This is further exacerbated by efforts to simplify the bureaucracy that have not been fully supported by increasing the ability and mastery of technology, which has the potential to hinder efficiency in public services. This article aims to analyze and describe 1) How the match between the composition and competency of the State Civil Apparatus affects the productivity of the bureaucracy in Indonesia; and 2) evaluate the effectiveness of bureaucratic simplification and equalization of positions in increasing the efficiency of decision-making and matching the composition of ASN with the existing workload. The research method used is a qualitative method. The data analysis used is an interactive model analysis consisting of three analysis components, namely: 1) Data Reduction; 2) Data Presentation; 3) Data Verification and Conclusion Drawing. The results of the article show that: 1) the mismatch between the composition and competency of ASN is still a major challenge in increasing the productivity of the bureaucracy in Indonesia. Countries with efficient bureaucratic systems such as Singapore and Estonia show that ASN placement based on strict competency evaluation can optimize performance, even though the age of the ASN is older. Therefore, Indonesia needs to adopt a more comprehensive approach, such as a continuous training system that is tailored to the needs of specific sectors, to improve the quality of ASN and streamline the bureaucratic structure to achieve higher productivity; 2) bureaucratic simplification and job equalization can match the composition of ASN with the workload more efficiently, allowing for faster and more responsive decision-making. An early retirement scheme can be a solution to replace less adaptive ASN with a workforce that is better prepared to face the challenges of technology and organizational dynamics. However, the success of bureaucratic simplification depends on the competence of the remaining ASN, who must be ensured to have skills that match the demands of change and the needs of the organization.